Pemantauan Perilaku Reaksi Kimia di dalam Eco Enzyme - Obi Januardi, Darius (AI Society & STMIK Indonesia, 2025)
Organic waste has become a serious environmental issue, with production reaching 20.23 million tons per year in Indonesia. This research offers an innovative solution through the eco enzyme method and Internet of Things (IoT) technology to monitor chemical reactions during the fermentation process in real-time using sensors and a website. The research compares two samples: a mixture of orange peels, papaya, pineapple, and Javanese sugar; and pineapple peels, water, and molasses (sugarcane syrup). Each used 2.1 kg of organic waste, 700 g of sugar, and 7,000 ml of water. During the 60-day fermentation period, the first sample produced gases such as Methane (CH4), Hydrogen Sulfide (H2S), Ammonia (NH3), Carbon (CO), and Hydrogen (H2), while the second sample produced Methane (CH4), Hydrogen Sulfide (H2S), Ammonia (NH3), and Nitrogen Oxide (NO2). there are also parameters measured such as pH and temperature. research shows that raw materials affect the gas produced, as well as utilizing IoT technology for more efficient and sustainable waste management.